Revenue Generation and Performance of Local Governments in Anambra State 2015-2024 - Nzekwe-Chinwuko, Fidelia Ifeyinwa (Asian Journal of Law and Islamic Finance, 2025)
The study used a descriptive survey design to examine revenue generation patterns across six local governments in Anambra State. Covering communities from all senatorial zones, it drew insights from a population of 1,919,000 and a sample of 400 respondents selected through purposive and proportional sampling. Data were collected using a validated and reliable structured questionnaire. Both descriptive statistics and multiple regression analyses were performed using SPSS 20, enabling the study to identify key factors influencing local government revenue performance. Low revenue generation was found to significantly weaken the performance of local governments in Anambra State. Most respondents agreed that inadequate revenue severely affects infrastructure provision, increases dependence on statutory allocations, and undermines financial sustainability. While some items showed moderate effects, the overall results indicated a high negative impact, with 41.38 percent rating the effect as high and 29.02 percent as moderate. Hypothesis testing further confirmed a significant relationship between low revenue and poor performance (t = 6.321, p < 0.00). The study therefore concludes that low internally generated revenue has a strong, negative influence on service delivery and governance effectiveness in the state. The study concludes that weak revenue generation significantly undermined the performance of local governments in Anambra State between 2015 and 2024. Low internally generated revenue limited infrastructure development, increased reliance on statutory allocations, and reduced governance efficiency. Strengthening revenue systems and improving financial autonomy are essential for better local government performance.